2012
DOI: 10.1159/000339502
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Heat Shock Protein 27 Antibody Titers and Prooxidant-Antioxidant Balance in Patients with Beta-Thalassemia Major

Abstract: Objective: Determination of the serum heat shock protein 27 (Hsp27) antibody titers and prooxidant-antioxidant balance (PAB) in patients with thalassemia as markers of cell and oxidative stress, respectively. Methods: Serum PAB and anti-Hsp27 antibody titers were measured in 140 patients with thalassemia major and 140 sex- and age-matched healthy volunteers. Results: A significantly higher serum PAB value was observed in patients in comparison to controls. In the patient group, anti-Hsp27 antibody titers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 115 publications
0
1
0
Order By: Relevance
“…[ 18 ], included 90 patients with BTM and 90 healthy individuals (control group) and demonstrated increased levels of PAB and ferritin in the patients compared with the controls; however, there was no significant relationship between these two indicators in their study. In addition, several other case-control studies have examined PAB- and BTM-related variables [ 19 - 21 ]. This present cross-sectional study showed a direct association between oxidative stress and serum-ferritin levels.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ], included 90 patients with BTM and 90 healthy individuals (control group) and demonstrated increased levels of PAB and ferritin in the patients compared with the controls; however, there was no significant relationship between these two indicators in their study. In addition, several other case-control studies have examined PAB- and BTM-related variables [ 19 - 21 ]. This present cross-sectional study showed a direct association between oxidative stress and serum-ferritin levels.…”
Section: Discussionmentioning
confidence: 99%